Blood pressure and urine output during the first 120 h of life in infants born at less than 29 weeks' gestation related to umbilical cord milking. Issue 5 (16th February 2009) - Hosono, S; Mugishima, H; Fujita, H; Hosono, A; Okada, T; Takahashi, S; Masaoka, N; Yamamoto, T
Abstract : Objective: To investigate the effects of umbilical cord milking on cardiopulmonary adaptation in very low birth weight infants. Patients and methods: This study was the secondary analysis of a randomised control study of the effect of umbilical cord milking in premature infants. Forty singleton infants born between 24 and 28 weeks' gestation were randomly assigned to groups in which the umbilical cord was clamped either immediately after birth (control group, n = 20) or after umbilical cord milking (milked group, n = 20). Blood pressure, heart rate, urine output, fluid intake, and ventilatory index values in both groups were measured during the first 120 h after birth. Results: There were no significant differences in gestational age or birth weight between the two groups. The initial haemoglobin value was higher in the milked group (mean (SD) 16.5 (1.4) g/dl in the milked vs 14.1 (1.6) g/dl in the control; p<0.01). During the first 12 h, blood pressure was significantly higher in the milked group. Urine output in the milked group was higher than that in the control group during the first 72 h. There were no significant differences in heart rate, water intake, or ventilatory index values between the groups. Conclusion: Umbilical cord milking may facilitate early stabilisation of both blood pressure and urine output in very low birth weight infants.